Transformational leadership and employee performance in hospitals: An Explanatory Survey with Path Analysis Approach - Syaiful Bachri; Abubakar Betan; Samila Samila; Yenny Sima; Abdullah Abdullah; Nur Anbiya (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Leadership plays a critical role in improving employee performance in hospital organizations, yet empirical evidence regarding its direct and indirect mechanisms remains inconsistent. This study examines how transformational leadership influences employee performance through knowledge sharing and teamwork creativity. Research Methodology: A quantitative explanatory survey was conducted among 123 hospital employees selected through purposive sampling. Data were collected using structured questionnaires and analyzed using path analysis to assess direct and indirect relationships among variables. Mediation effects were tested using the Sobel test at a 5% significance level. Results: Transformational leadership did not have a significant direct effect on employee performance (p > 0.05). However, it significantly influenced knowledge sharing and teamwork creativity (p < 0.001). Both mediating variables demonstrated strong positive effects on employee performance. Mediation analysis confirmed full mediation, indicating that leadership improves performance indirectly through enhanced knowledge exchange and creative teamwork. The model explained a substantial proportion of variance in employee performance. Conclusion: Leadership effectiveness in hospitals depends on fostering collaborative knowledge sharing and stimulating team creativity rather than relying solely on inspirational attributes. Strengthening knowledge management systems and fostering innovation-oriented teamwork are essential to improving organisational performance,